Sistem Pembayaran Parkir Non-Tunai Berbasis Mikrokontroler dengan Metode Template Matching - Egita Lorenza K; Rian Ferdian; Desta Yolanda (CHIPSET, 2023)
Parking is an activity to stop or store vehicles in a place that has been provided in public places that have a parking system. The parking system is a system that is applied to a parking environment. Several parking systems developed are manual parking systems, computer-based parking systems, semi-automatic parking systems and RFID-based parking systems. Indonesia has developed a lot of computer-based parking systems, but many areas still use manual parking systems. So that there are still many vehicles parked carelessly, security is not guaranteed and the payment system has not been accumulated based on the length of parking time. This paper describes the development of a parking system based on the template matching method by developing non-cash payments based on the length of parking time. Researchers use a webcam to detect vehicles that will enter the parking area. The captured images are processed in a database to store vehicle entry time information. Researchers use qr codes as a substitute for admission tickets. When leaving the parking area, a QR code will be scanned on the provided application, then users can make payments through the application. This system can be carried out independently by the user so that it does not require full 24-hour supervision.